2003
DOI: 10.1002/crat.200310053
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric twinning crystals of Zinc oxide formed in a hydrothermal process

Abstract: Well crystallized ZnO powders with various morphologies such as hour glass-shaped, shortened prismatic, flake-like and prismatic form have been synthesized by adopting the system of Zn(Ac) 2 -KOH-H 2 O via a hydrothermal process at 200°C for 2 h. It was found that the as-synthesized hour glass-shaped ZnO crystallites are asymmetric both in shape and stoichiometry: while the atomic ratio of O/(Zn+O) at the bigger end ranges from about 60% to 40% along the polar axis of the hour glass-shaped ZnO crystallites, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…LiOH, NaOH, etc) [28]. There are reports of modifications of the ZAH dehydration or dissolution and subsequent condensation for the growth of ZnO nanostructures [29][30][31]. The search for primary clusters to serve as building blocks for various nanostructures has been going on for quite some time.…”
Section: Zah Based Sol-gel Synthesis Of Zno Nanostructuresmentioning
confidence: 99%
“…LiOH, NaOH, etc) [28]. There are reports of modifications of the ZAH dehydration or dissolution and subsequent condensation for the growth of ZnO nanostructures [29][30][31]. The search for primary clusters to serve as building blocks for various nanostructures has been going on for quite some time.…”
Section: Zah Based Sol-gel Synthesis Of Zno Nanostructuresmentioning
confidence: 99%
“…Normally aqueous solutions are used, and the process is then referred to as a hydrothermal growth process. Some of the solution-phase synthesis processes include a zinc acetate hydrate (ZAH)-derived nanocolloidal sol-gel route [12], ZAH in an alcoholic solution with sodium hydroxide (NaOH) or tetra methyl ammonium hydroxide (TMAH) [13][14][15], template-assisted growth [16], spray pyrolysis [17,18] and electrophoresis [19] for fabricating nanostructured thin films.…”
Section: Introductionmentioning
confidence: 99%
“…2 Very recently, we reported that annealing at 900°C could completely transform the ZnO nanorods with diameters of ϳ10 nm and lengths of ϳ100 nm into twinning morphologies comprising two quasispheres. 8 While twinning is a common feature in jointed ZnO nanostructures, [9][10][11][12][13][14][15] especially in that prepared by thermal evaporation, [12][13][14][15] the present work reveals that the annealed products of ZnO nanorods are indeed twinning free. The lattice images of two jointed grains show the same plane, but the alignment is random.…”
mentioning
confidence: 52%